Giant Renal Angiomyolipoma without Fat Density on CT Scan: Case Report and Review of the Literature - Kenneth G. Nepple; Nathan A. Bockholt; Laila Dahmoush; Richard D. Williams (The Scientific World Journal)
Giant renal angiomyolipomas have been reported, but typically have the pathognomonic finding of fat density on CT scan. We present the case of a 53-year-old male with a symptomatic, 35-cm, predominantly cystic renal mass without fat density on CT that on nephrectomy was found to be a fat-poor angiomyolipoma with predominantly epithelioid morphology weighing 17.9 kg. Giant renal angiomyolipoma without macroscopic fat density on CT scan is an exceedingly rare occurrence.